THE EFFECT OF GUIDED NOTE TAKING ASSISTED SELF REGULATED LEARNING MODEL TOWARDS THE PHYSICS LEARNING ACHIEVEMENT OF AN SMP STUDENTS - ., Ni Wayan Yusti Purnadewi; ., Prof. Dr. I Wayan Santyasa,M.Si; ., Drs. I Nyoman Putu Suwindra, M.Kom. (Jurnal Pendidikan Fisika Undiksha, 2014)
Penelitian ini bertujuan untuk menganalisis perbedaan prestasi belajar fisika antara kelompok siswa yang belajar dengan model self regulated learning berbantuan guided note taking (SRLMA), kelompok siswa yang belajar dengan model self regulated learning (SRLM) dan kelompok siswa yang belajar dengan model pembelajaran Konvensional (CLM). Jenis penelitian ini adalah eksperimental semu dengan desain penelitian nonequivalent pretest-posttest control group design. Variabel bebas pada penelitian ini adalah SRLMA, SRLM dan CLM sedangkan variabel terikatnya adalah prestasi belajar fisika siswa. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 2 Abiansemal tahun pelajaran 2013/2014 yang terdiri dari 9 kelas dengan jumlah populasi 308 siswa. Sampel kelompok diambil dengan teknik simple random sampling. Jumlah sampel dalam penelitian ini adalah 103 siswa.Teknik pengumpulan data dilakukan dengan pretest dan posttest. Data prestasi belajar fisika siswa dianalisis secara deskriptif dan analisis ANACOVA satu jalur, dengan pengujian taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa terdapat perbedaan prestasi belajar antara siswa yang belajar dengan menggunakan SRLMA, SRLM, dan CLM (F = 20,782 dan α = 0,001). Prestasi belajar siswa yang belajar dengan menggunakan SRLMA berada pada kualifikasi cukup (M = 64,00; SD = 6,43), yang belajar dengan menggunakan SRLM berada pada kualifikasi cukup (M = 59,00; SD = 6,09), dan yang belajar dengan menggunakan CLM berada pada kualifikasi kurang (M = 54,60; SD = 5,80). Hasil tindak lanjut uji LSD menunjukkan bahwa prestasi belajar siswa yang belajar dengan model SRLMA lebih tinggi dibandingkan SRLM ( ; Δµ= 3,628). Prestasi belajar siswa yang belajar dengan SRLMA lebih tinggi dibandingkan CLM ( ; Δµ=8,211). Prestasi belajar siswa yang belajar dengan SRLM lebih tinggi dibandingkan CLM (LSD = 2,856; Δµ=4,853). Kata Kunci : model self regulated learning, prestasi belajar, model pembelajaran konvensional, guided note taking This study aimed at analyzing the difference of students’ achievement among the students who studied by using Guided Note Taking Assisted Self Regulated Learning Model (SRLMA), Self Regulated Learning Model (SRLM), and Conventional Learning Model (CLM). This study was quasy experiment with non equivalent pretest-posttest control group design. The independent variables of this research were the SRLMA, SRLM, and CLM with prior students’ achievement as covariate, while the dependent variable was physics students’ achievement. The population of this research was the whole grade VIII students of SMP Negeri 2 Abiansemal in academic year 2013/2014 which consisted of 308 students from 9 classes. Groups of sample were taken by using simple random sampling technique. The amount of the samples were 103 students. Data were collected by using pretest and posttest. Data of students’ achievement were analyzed descriptively and used one way ANCOVA analysis. For further analysis, Least Significant Difference (LSD) was used with significant evaluation test level 0.05. The result of this study shows that there are students’ achievement differences among students of SRLMA group, SRLM group, and CLM group (F= 20.782 and α= 0.001). The students’ achievement on the SRLMA students was considered as medium category (M=64.00 and SD=6.43), the students’ achievement on the SRLM group was considered as medium category (M=59.00 and SD=6.09), while the students’ achievement on the CLM students was considered as low category (M=54.60 and SD=5.80). This result shows that the students’ achievement of the SRLMA group was higher than the SRLM group and CLM group. LSD analysis shows that the students’ achievement of SRLMA group is better than SRLM group (LSD=2.877; =3.628), the students’ achievement of SRLMA group is better than CLM group (LSD=2.856; =8.211), and the students’ achievement of SRLM was higher than CLM group (LSD=2.856; =4.853).keyword : Self regulated learning model, Learning achievement, Guided note Taking, Conventional Learning Model